Current Perspectives on Anti-Infective Agents. - Tamreihao, K.; Mukherjee, Saikat; Niṃthaujama, Debānanda Esa., 1961- (Frontiers in Anti-Infective Agents, 2019)
The volume is a comprehensive documentation on major infectious diseases from tropical countries which pose a serious threat to global healthcare programs. These include diseases such as tuberculosis, AIDS, leishmaniasis (kala-azar), elephantiasis, malaria, leprosy, various fungal disorders and emergent viral diseases. Due to the widespread use of antibiotics, there is an emergence of drug resistant pathogens in many regions. Hence, there is a need to search for novel, cost-effective bioactive compounds that demonstrate high efficacy and low toxicity in human cells from unexplored ecosystems t.